Self-perception and oral health in pregnant adolescents - Rovida, T. A. Saliba; Moimaz, S. A.; Lima, D. P. [UNESP]; Garbin, C. A. Saliba (Oral Health And Dental Management, 2014)
To evaluate the oral health indicators by determining the experience of dental caries and periodontal disease and identification of self-perceived oral health status of pregnant adolescents and to assess the association between the studied variables. A transversal study, survey type and survey of the oral health status of 127 adolescents, 10-19 years of age, pregnant, accompanied by the Unified Health System of Araçatuba-SP was performed. The self-perceived oral health and socio-demographic data were recorded using an adapted questionnaire. The oral health statuses were analyzed using the DMFT and CPI indices in accordance with the criteria established by the WHO for epidemiological survey. Descriptive statistical analyzes and the Fisher's exact test with a significance level of 5% was performed, as well as a logistic regression analysis to verify the association between the variables. Of the total, 41.0% reported having satisfactory oral health, while 63.0% believed they had problems with their teeth and gums. The DMFT index was 12.51 (SD = 4.21). The percentage of caries-free was 6.3%, and 91.3% had periodontal problems. A statistically significant association was found between the variables: self-perceived oral health and periodontal disease p = 0.0166 and self-reported gum disease and periodontal disease p = 0.0039. Most patients considered their oral health as poor and reported having dental and gum problems, which can also be observed in the clinical examination since the caries experience of the pregnant women examined was considered high and the symptoms of periodontal disease were observed in most of the volunteers.